Analysis of the Character Value of Caring for the Environment as Culture in SDN Kedungturi in Adiwiyata School: Analisis Nilai Karakter Peduli Lingkungan Sebagai Budaya Di SDN Kedungturi Dalam Sekolah Adiwiyata - Islamiyah, Safirah; Setiyawati, Enik (Indonesian Journal of Education Methods Development, 2020)
The objectives of this study to describe the character value and its barriers of environmental caring habit in SDN Kedungturi of Adiwiyata. Phenomenological qualitative method is applied, the background of study related to the common phenomenon such in researcher's sorrounding.The primary data are chunks and behavior white documents and thers are as supporting data. Applicable technique is triangulation which are observation, depth-interview and documentation. From the six indicators analysed, two levels of application are found the high and medium. Researcher has been determined students whose environmental ambassador label have got intensive habit and environmental knowledge from their teachers very well. As a result, those students become role model for their friends, so that the environment caring as character value in SDN Kedungturi able to work effectively.